Implementation of accelerated research: strategies for implementation as applied in a phase 1 Ad26.ZEBOV, MVA-BN-Filo two-dose Ebola vaccine clinical trial in Uganda. Issue 1 (31st December 2020) - Kitonsa, Jonathan; Ggayi, Abu-Baker; Anywaine, Zacchaeus; Kisaakye, Eva; Nsangi, Laura; Basajja, Vincent; Nyantaro, Mary; Watson-Jones, Deborah; Shukarev, Georgi; Ilsbroux, Ine; Robinson, Cynthia; Kaleebu, Pontiano
ABSTRACT: Background: The 2013–2016 Ebola epidemic in West Africa is the worst ever caused by Ebolaviruses with over 28, 000 human cases and 11, 325 deaths. The World Health Organisation (WHO) declared the epidemic a public health crisis that required accelerated development of novel interventions including vaccines. The Medical Research Council/Uganda Virus Research Institute and London School of Hygiene and Tropical Medicine Uganda Research Unit (MRC/UVRI & LSHTM Uganda Research Unit) was among the African research sites that implemented the VAC52150EBL1004 Ebola vaccine trial. Objective: We report on the strategies utilised by the Unit and sponsor in ensuring expedited clinical trial approval and accelerated conduct. Methods: Janssen Vaccines and Prevention B.V. conducted a phase 1 trial to evaluate the safety, tolerability, and immunogenicity of heterologous two-dose vaccination regimens using Ad26.ZEBOV and MVA-BN-Filo, in healthy adults in Africa. Accelerated implementation strategies are hereby presented. Results: Strategies included: holding the African Vaccine Regulatory Forum (AVAREF) joint review meeting; expedited review by institutional ethics and country-specific regulatory bodies; competitive recruitment between sites; electronic data capture (EDC); frequent study monitoring schedule; involvement of a community advisory board (CAB); and utilization of a 'phased' study information-sharing approach in community engagement and participant recruitment. These strategies enabled the site to acquire approvals within 2 months and enrol 47 participants within a spurn of five. The same milestone is usually acquired in at least 1 year without accelerated implementation. Conclusion: The use of well-thought strategies by sponsors and research sites can enable the implementation of accelerated research. We recommend the use of similar strategies in other settings.